Measurement of the cross section for open-beauty production in photon–photon collisions at LEP - Dova, María Teresa (2005)
The cross section for open-beauty production in photon–photon collisions is measured using the whole high-energy and high-luminosity data sample collected by the L3 detector at LEP. This corresponds to 627 pb−1 of integrated luminosity for electron–positron centre-of-mass energies from 189 to 209 GeV. Events containing b quarks are identified through their semi- leptonic decay into electrons or muons. The e+e− → e+e−bbX cross section is measured within our fiducial volume and then ̄ extrapolated to the full phase space. These results are found to be in significant excess with respect to Monte Carlo predictions and next-to-leading order QCD calculations.